2023
DOI: 10.3390/ijms241713429
|View full text |Cite
|
Sign up to set email alerts
|

Tear Biomarkers and Alzheimer’s Disease

Snježana Kaštelan,
Marijana Braš,
Neda Pjevač
et al.

Abstract: Alzheimer’s disease (AD) is an age-related progressive neurodegenerative brain disorder that represents the most common type of dementia. It poses a significant diagnostic challenge that requires timely recognition and treatment. Currently, there is no effective therapy for AD; however, certain medications may slow down its progression. The discovery of AD biomarkers, namely, magnetic resonance imaging, positron emission tomography and cerebrospinal fluid molecules (amyloid-β and tau) has advanced our understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Recent advances in AD biomarkers include tear markers, which are non-invasive. Tears are non-invasive biological fluid, easy to collect and can be stored for extended periods, certain amount of diseases can be assessed using tear markers in place of other biomarkers, including keratoconus, Parkinson disease, cystic fibrosis and thyroid disease 10 . Studies show that diagnostic biomarkers such as Aß42 and p-tau, which are found in tears, are under investigation for their cost-effectiveness.…”
Section: Main Textmentioning
confidence: 99%
“…Recent advances in AD biomarkers include tear markers, which are non-invasive. Tears are non-invasive biological fluid, easy to collect and can be stored for extended periods, certain amount of diseases can be assessed using tear markers in place of other biomarkers, including keratoconus, Parkinson disease, cystic fibrosis and thyroid disease 10 . Studies show that diagnostic biomarkers such as Aß42 and p-tau, which are found in tears, are under investigation for their cost-effectiveness.…”
Section: Main Textmentioning
confidence: 99%
“…The TearAD study aimed to use tear fluid as a potential source of AD biomarkers. In previous reports, it was demonstrated that the AD biomarkers amyloid-beta and tau are measurable in tear fluid and are associated with disease severity and neurodegeneration [ 126 ]. This study aimed to validate the previous results in a larger cohort and evaluated the diagnostic accuracy of tear biomarkers when discriminating between individuals with and without neurodegeneration, as determined by hippocampal atrophy [ 126 ].…”
Section: Biosensing In Body Fluidsmentioning
confidence: 99%
“…Additionally, many of these tests are associated with negative side effects such as radiation exposure from PET scans [68]. Finding a simple and non-invasive method that can be frequently administered for early AD or MCI diagnosis could provide an opportunity for those affected by AD to receive treatment that slows progression [68][69][70][71]. Furthermore, early detection biomarkers can be used to screen for individuals at a high risk of AD.…”
Section: Cognitive Function In Aging and Admentioning
confidence: 99%